THE LATEST APPLICATION OF TUBIFEX AS LIVE FEED IN AQUACULTURE - Simangunsong, Tohap; Anjaini, Jefri; Situmorang, Nurbaity; Liu, Chun-Hung (Journal of Environmental Engineering and Sustainable Technology, 2023)
The food industry with the fastest rate of growth in more than 50 years is the fisheries sector. The sector of aquaculture and capture has grown to be very promising. In order to support the success of this business, the aquaculture industry in freshwater and marine environments is currently progressing. In the larval stage, choosing fish feed that is of high quality is crucial. The primary food source for fish larvae to support the growth and development of farmed fish is natural feed with a high protein content. Numerous varieties of farmed fish and ornamental fish have been fed Tubifex tubifex, a natural silkworm food. Protein and fat content in this polichaeta class worms are respectively 66% and 12%. When farmed fish are growing and developing, the high protein content of these worms may serve as their primary source of protein. Several initiatives are currently being made to enhance worm protein quality by consuming more food that contains macro- and micronutrients. Agricultural waste that has fermented or decomposed, which is typically regarded as waste, has nutritional value that can be combined with mud or sand to keep worms for a while. The nurture of fish larvae or fry may one day be possible using silkworms.